’n Skoolhoof se persepsies van die verwesenliking van Christelike waardes in ’n Suid-Afrikaanse laerskool: ’n Gevallestudie - Steyn, Gertruida M. (Koers, 2012)
A principal’s perceptions of the realisation of Christian values at a South African Primary School: A case study.Many South African schools are facing the challenge of establishing a school culture that is conducive to teaching and learning. The school culture has a far greater impact on living and learning than any other factor in the life of a school. The research question in this study is: How did a primary school principal view the actualisation of Christian values in the school culture? An investigative, qualitative research design, and more particularly a case study, was considered to be the most appropriate approach to the research question. In a number of previous investigations in the school, the author has shown that the school principal treasured the inculcation of Christian values in the school. Data in this study were collected by means of various semi-structured interviews with the principal; paragraphs written by the principal; documents about school activities; a DVD of the school; and field notes taken during the interviews. The findings show the role of the principal in inculcating values in a school and the effect of a vision and mission to realise these values. Inculcating values in a school is best actualised in a positive, inviting school culture that focuses on continuing growth conducive to human development.